The establishment of municipal boundaries in São Paulo's territorial sea and its impact on the distribution of natural resources and on environmental and social rights and co-responsibilities - Oliveira, Rosângela Célia Ribeiro de; Xavier, Ana Fernandes; Paludo, Danielle; Campos, Fausto Pires de; Campos, Fausto Rosa de; Costa, Hubert Bayer (Seven Editora, 2023)
The creation of three Marine Environmental Protection Areas by the Secretary of the Environment of São Paulo, in 2008, totaling 1,138,067.68 hectares, extending from Ubatuba to Cananéia, in the coastal marine zone of São Paulo, raised the issue of formalizing the Waters Courts in 15 municipalities in the State and the respective rights and responsibilities. We present a proposal for this division of interests and duties at Sea, with a map establishing preliminary boundaries for future deliberations in society. We describe the process and bases for proposing Marine Environmental Protection Areas and present their main data. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-110